2020
DOI: 10.14311/ctj.2020.2.04
|View full text |Cite
|
Sign up to set email alerts
|

The Change of Cardiostimulation Device Programming Due to Detection of Electromagnetic Interference

Abstract: The study deals with the interdisciplinary topic of the electromagnetic compatibility of the cardiac implantable electronic devices that are used in patients with a defect of heart conduction system. We are focusing on the detection of disturbing signals on electrodes of cardiostimulation device and its interpretation. The detection of electromagnetic interference (EMI) is related to electrode choice, device placement, its configuration and programming. The aim of the study is the analysis of the pacemaker res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 4 publications
0
4
0
1
Order By: Relevance
“…The shape of the ventricular electrode was semicircular with a total area of 225 cm 2 , which represents the maximum achievable effective induction area formed by the electrode, as described in [8]. For dual-chamber devices, the shape of the atrial electrode corresponded to frequent fixation in the right atrial appendage [9].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The shape of the ventricular electrode was semicircular with a total area of 225 cm 2 , which represents the maximum achievable effective induction area formed by the electrode, as described in [8]. For dual-chamber devices, the shape of the atrial electrode corresponded to frequent fixation in the right atrial appendage [9].…”
Section: Methodsmentioning
confidence: 99%
“…Current trend is effort to minimize a risk associated with EMI, although it is not possible to completely eliminate it [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…Such as: M: represents a square matrix (N * N), whose elements "m_ (N, N)" are numerical coefficients depending on the N unknowns (V_ (1), ...V_N), involved in the equations of the system (6).…”
Section: Paper-in Vitro Modeling Of Implantable Cardiac Pacemakers Submitted To Conducted Disturbancementioning
confidence: 99%
“…J. Morava and A. Richter in 2020, they showed that ICEDs are subject to incorrect interpretation of electrical signals, because the device does not monitor the shape of the detected signal, according to which it can distinguish between interference and arrhythmias. Thus, the presence of electromagnetic interference signals can also cause temporary modifications to its programming and can easily affect its performance [6]. The MAUDE (The Manufacturer and User Facility Device Experience) database of the US Food and Drug Administration identified 2843 cases of medical device malfunctions induced by EMPs, between January 2010 and March 2017 [7].…”
Section: Introductionmentioning
confidence: 99%
“…Pokud se pacient s CIED setká se zdrojem elektromagnetického pole (EMP), může za určitých okolností emitované pole ovlivnit funkci srdečního přístroje, což může mít pro pacienta vážné důsledky. [1,2,4] Mezi potenciálně nebezpečné zdroje patří také technika pro svařování elektrickým obloukem. Zdroj svařovacího proudu je schopen generovat stovky ampér a být tak zdrojem silného magnetického pole.…”
unclassified